Data from a dynamic simulation in a free-floating and continuous regime of a solar greenhouse modelled in TRNSYS 17 considering simultaneously different thermal phenomena - Baglivo, Cristina (Data Brief, 2020)
This dataset supports the research article “Complete greenhouse dynamic simulation tool to assess the crop thermal well-being and energy needs” [1]. In the agricultural sector, the use of energy can be very intensive [2] and the simulation of solar greenhouses is a very complex work [3]. This dataset provides the results of thermal modeling and dynamic simulation of a solar greenhouse considering simultaneously several thermal phenomena. The analysis was performed by TRNSYS 17 software (TRaNsient SYstem Simulation). The results obtained consider different phenomena that affect the thermal behavior of the greenhouse, including evapotranspiration produced by plants, heat exchange with the soil and the presence of artificial lights. Different models are presented for the calculation of the convective coefficient that best suits the presence of glass surfaces, considering the different discretization of the internal volume (single thermal zone and twenty thermal zones). The parameters that influence the thermal behavior of the greenhouse are analyzed on an hourly basis, the model has been validated with EnergyPlus. The data allow the researcher to choose a suitable greenhouse model in the case of free-floating model or in the presence of an air conditioning system.